2022
DOI: 10.1021/acs.jpclett.2c01270
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Carrier Relaxation Dynamics in Heterovalently (Bi3+) Doped CsPbBr3 Nanocrystals

Abstract: Manipulation of intrinsic carrier relaxation is crucial for designing efficient lead halide perovskite nanocrystal (NC) based optoelectronic devices. The influence of heterovalent Bi 3+ doping on the ultrafast carrier dynamics and hot carrier (HC) cooling relaxation of CsPbBr 3 NCs has been studied using femtosecond transient absorption spectroscopy and first-principles calculations. The initial HC temperature and LO phonon decay time point to a faster HC relaxation rate in the Bi 3+ -doped CsPbBr 3 NCs. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 61 publications
(158 reference statements)
3
57
1
Order By: Relevance
“…The TA spectra with varying delay times and the corresponding 2D pseudocolor plot of RPP in the presence of TP ligands are shown in Figure S9. Pure 2D RPPs show the ground-state bleach (GSB) peak at around 435 nm due to band edge state filling, 11,23,27,36 which closely matches the absorption spectra. It is noteworthy that both electrons and holes are responsible for the GSB of RPP.…”
Section: ■ Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The TA spectra with varying delay times and the corresponding 2D pseudocolor plot of RPP in the presence of TP ligands are shown in Figure S9. Pure 2D RPPs show the ground-state bleach (GSB) peak at around 435 nm due to band edge state filling, 11,23,27,36 which closely matches the absorption spectra. It is noteworthy that both electrons and holes are responsible for the GSB of RPP.…”
Section: ■ Introductionmentioning
confidence: 56%
“…Organic–inorganic hybrid halide perovskites have gained significant research interest in the last decade for improving the efficiency of photovoltaic devices. They have unique photophysical properties such as large absorption coefficient, small exciton binding energy, , high charge transport mobility, , long charge carrier diffusion lengths, , and high quantum efficiency. , The critical issue of such perovskite materials is stability, and various strategies have been considered to improve the stability. The general formula of Ruddlesden Popper perovskites (RPP) is (RNH 3 ) 2 A n –1 M n X 3 n +1 ( n = 1, 2, 3, 4......), where RNH 3 is a large organic alkylammonium spacer cation, A is a monovalent organic cation, M is a divalent metal cation, X is a halide anion, and n represents the number of [MX 6 ] 4– octahedral layers within each quantum well. , The RPPs have opened new opportunities to tune their properties by tailoring the structural components.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, multiple photo-induced processes occur in the PNPs within the same time scale. An advanced spectro-temporal parameterization, namely global target analysis, is required for interpreting all the plausible relaxation processes at various timescales and exact spectral signatures of the involved excited-state species. , Therefore, we have performed a global target analysis of the fsTA for all samples. The complete picture of the excited-state dynamics with all the plausible excited-state relaxation processes is depicted in Figure A–C.…”
Section: Resultsmentioning
confidence: 99%
“…Dopant-induced hole trap states have been broadly observed in many different materials. For example, in silver- and copper-doped semiconductor NCs, the photogenerated holes were found to be rapidly localized within covalent [MSe 4 ] dopant clusters (M = Ag + , Cu + ), which mainly act as the deep hole trap states . For Bi-doped CsPbBr 3 materials, Bi-doping-induced defects have also been confirmed by lots of experimental studies. ,, A recent theoretical study by Cai et al further found that the formation energies of Bi Pb (Bi atoms replaces Pb atoms) and Bi i (Bi atoms in the interstices) defects are smaller than that of the Bi Cs (Bi atoms replaces Cs atoms) defect, indicating that the Bi Pb and Bi i defects are more stable than the Bi Cs defect . Therefore, the hole trap states in Bi-doped NCs might be mainly related to Bi Pb and Bi i structural defects.…”
mentioning
confidence: 90%
“…51 For Bi-doped CsPbBr 3 materials, Bi-dopinginduced defects have also been confirmed by lots of experimental studies. 39,50,53 A recent theoretical study by Cai et al further found that the formation energies of Bi Pb (Bi atoms replaces Pb atoms) and Bi i (Bi atoms in the interstices) defects are smaller than that of the Bi Cs (Bi atoms replaces Cs atoms) defect, indicating that the Bi Pb and Bi i defects are more stable than the Bi Cs defect. 38 Therefore, the hole trap states in Bi-doped NCs might be mainly related to Bi Pb and Bi i structural defects.…”
mentioning
confidence: 99%